My enemy or my brother? Spanish representations of Muslim and Jewish culture during the colonial campaigns in Morocco, 1909-1927 - Allard, E (2016)
This thesis examines Spanish representations of Muslim and Jewish cultures in Morocco during the colonial campaigns in the Rif (1909-1927) in relation to constructions of Spanish identity during this period. It focuses on visual and textual narratives in the press (colonial photojournalism) and on three literary texts: Carmen de Burgos' En la guerra (1909), Ernesto Giménez Caballero's Notas marruecas de un soldado (1923) and Arturo Barea's La ruta (1943). The analysis undertaken centres on the use of the motifs of the body and the city and references to the medieval Castilian ballad tradition, the Romancero, by writers and photographers to explore the cultural relationship between Spain and North Africa. The chapters explore the delineation of boundaries between Spanish and Moroccan cultures by contemporary commentators and the power structures that underpin those boundaries, considering the different hierarchies that are established in Spain’s relationship with Moroccan Muslims and Jews. Chapter 1 concerns the socio-historical context of the colonial campaigns and highlights the significance of the question of Spain’s identity in relation to Morocco during this period. Chapter 2 compares representations of cultural and ethnic affinity between Spain and Morocco, arguing that beyond merely serving as a tool of colonial domination, they are harnessed in some cases to support the colonial venture, in others to challenge it, and yet in others to explore the pre-modern origins of the Spanish nation. In many of the examples examined, a process of self-Orientalisation is observed, where the 'Orientalist' and colonialist gaze is turned back on Spain as well as on Morocco. Chapter 3 examines representations of Muslim and Jewish alterity, arguing that these assertions of difference reveal Spanish anxieties about non-difference from North Africa, cultural regression, national fragmentation, and Spain's ability to dominate the protectorate. I conclude that these anxieties provide the fundamental underpinning to Spanish constructions of Morocco during the Rif War, and that this self-awareness about non-difference and failures of domination unsettles the predominant paradigm of discourse analysis within colonial studies.